2014
DOI: 10.1080/0972060x.2013.831555
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of the Essential Oils of Five IranianBuniumSpecies (B. lurestanicum, B. microcarpum, B. badghayzi, B. wolffiandB. carioides)

Abstract: The genus Bunium comprised 14 species in Iran, two of them (B. wolfi and B. lurestanicum) are endemic. Among these species, only B. persicum is famous and used in medicinal and nutrition industries. In this research, the essential of five Iranian Bunium species, named B. lurestanicum, B. microcarpum, B. badghayzi, B. wolffi and B. carioides were studied. At first, different parts of these plants were collected from their habitats; if possible the plant parts were separated and then dried. The dried plant ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…The oils isolated by hydro‐distillation from the fruits of B cylindricum , B paucifolium , B persicum and B wolffii were pale yellow to colourless, and the levels of the average yields were recorded 0.79%, 0.16%, 2.42% and 1.80% (w/w) respectively based on dry weights (Table 2). These results are in close conformity with previous findings on B persicum (0.5 to 1.6 and 2.5%) and B wolffii (1.90%) from other regions 6,8,28 . Sefidkon et al 13 reported that the fruits of B cylindricum and B rectangulum had the highest content of essential oils among plant organs.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The oils isolated by hydro‐distillation from the fruits of B cylindricum , B paucifolium , B persicum and B wolffii were pale yellow to colourless, and the levels of the average yields were recorded 0.79%, 0.16%, 2.42% and 1.80% (w/w) respectively based on dry weights (Table 2). These results are in close conformity with previous findings on B persicum (0.5 to 1.6 and 2.5%) and B wolffii (1.90%) from other regions 6,8,28 . Sefidkon et al 13 reported that the fruits of B cylindricum and B rectangulum had the highest content of essential oils among plant organs.…”
Section: Resultssupporting
confidence: 92%
“…Several studies analysing the essential oils of the fruits of B persicum from various regions and populations have mostly reported γ ‐terpinene (39.7%‐41.9%), γ ‐ terpinen‐7‐al (37.2%) and cumin aldehyde (37.1%) as the main components 2,33 . Sefidkon et al 6 reported 23 compounds in the essential oils of flowers and fruits of B wolffii with germacrene D (30.1%), β ‐ selinene (11.6%) and β ‐ pinene (8.1%) as main constituents. There are similarities and differences among the above‐cited reports and the present study (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations